A SOCIOLINGUISTIC ANALYSIS OF TABOO WORDS IN THE EMERGENCY 2022 MOVIE - Firda Aliffia; Wahyu Widianto; Sri Wahyuni (STKIP Subang, 2023)
This research focuses on the Sociolinguistic Analysis of Taboo Words in The Emergency 2022 Movie. The qualitative method used was content analysis. The data of this research were taken from the Emergency 2022 movie. The data was collected by watching the movie and reading the transcript, identifying and underlying the taboo words. The data were analyzed using Batistella's theory to describe the types of taboo words and Wardhaugh's theory to describe the function of taboo words. First, the result there are 143 taboo words used by characters with percentages for each type: epithet 16 instances (11.2%), profanity 22 instances (15.4%), vulgarity 10 instances (7%), and obscenity 95 instances (66.4%). The obscenity type is the most frequently used taboo word. Second, there are four functions, which can be seen in the movie with the following percentages: 23 cases (16.1%) to draw attention, 66 cases (46.1%) to show contempt, 51 cases (35.7%) to be provocative, and 3 cases (2.1%) to mock authority. The most common function in the Emergency 2022 film seems to be to show contempt.